Authoritarianism, Informal Law, and Legal Hybridity - Yilmaz, Ihsan. author. (orcid)0000-0001-8409-3045 Link aut Link
VII, 258 p. 1 illus.
Keywords: This book investigates Turkey’s departure from a ‘flawed democracy’ under Kemalist secularism, and its transitioning into Islamist authoritarian Erdoğanism, through the lenses of informal law, legal pluralism, and legal hybridity. In doing so, it examines the attempts of Turkey’s ruling party (AKP) at social engineering and gradual Islamisation of the Turkish state and society, by using informal Islamist laws. To that end, the book argues that the AKP has paved the way for Islamist legal hybridity where society, state, and law, are being gradually Islamised on an ad hoc basis. Informal law and legal pluralism in Turkey have had a non-state characteristic which have permitted Muslims to solve disputes by seeking the opinions of religio-legal scholars. Yet under the AKP rule, this informal legal system has become increasingly dominated by conservatives, sometimes radical Islamists, which the governing party has taken advantage of by either formalizing some parts of the informal Islamist law, or using it informally to mobilize its supporters against the opposition. Ihsan Yilmaz is Research Professor and Chair at the Alfred Deakin Institute for Citizenship and Globalisation, Deakin University, Melbourne, Australia. He has conducted mixed method research on authoritarianism, legal pluralism, nation-building, citizenship, Islam–state–law relations in majority and minority contexts (Turkey, Pakistan, Egypt, Indonesia, UK, USA and Australia), Islamism, populism, transnationalism, ethnoreligious and political minorities, securitisation, and intergroup relations. He was Professor of Political Science at Istanbul Fatih University (2008–2016), Lecturer in Law, Social Sciences and Politics at SOAS, University of London (2001–2008), and a fellow at Centre for Islamic Studies, the University of Oxford (1999–2001).